Verbal Idioms and Linguistic Distortions in Selected Fela Anikulapo’s Afrobeat Lyrics - James Oladunjoye Faleye; Anthony Olabiyi Adejuwon (Journal of linguistics, culture and communication, 2025)
Scholars have studied the linguistic choices in Fela’s lyrics. However, the peculiar verbal idioms and linguistic distortions that the artiste deploys to (re)socialise his audience to African realities have not been sufficiently interrogated. This study, therefore, is a postcolonial reading of his selected lyrics viewed through the lens of anti-language. It examines the verbal idioms and linguistic distortions in the lyrics and relates them to his ideological orientations. The data comprise 5 purposively selected lyrics downloaded from the internet: ‘International thief thief I. T. T’, ‘Teacher don’t teach me nonsense’, ‘Shuffering and Shmiling’, ‘Beasts of no nation’, and ‘Army arrangement’. These songs cut across the themes of corruption, culture as a teacher, and people’s existential difficulties. These downloaded lyrics are printed and subjected to critical analysis to identify samples of verbal idioms in them. The data were analysed with insights from anti-language and postcolonial theories. Findings show that Fela Anikulapo’s lyrics comprise verbal idiom and linguistic distortions that can be classified as anti-language because of his ideological stance on colonialism. The artist deploys peculiar verbal idioms which are products of relexicalisation processes: orthographic reconfiguration, phonological, syntactic, and morphological distortions comprising borrowing and reduplications. It concludes that the linguistic distortions in the verbal idioms are in tune with his anti-establishment ideological stance of reclamation of African values and the creation of a new social order.